Ex-ante impact of school feeding scaling on the Fatick (Senegal) local inclusive economy: An evaluation on income and employment - Fall, Modou Gueye; Ba, Koki; Ndour, Maimouna; Diene, Rokhaya; Faye, Daouda; Sall, Moussa; Diakhaté, Pape Bilal; Camara, Astou Diao; Cesaro, Jean-Daniel (2024)
The scaling up of school canteens in the commune of Niakhar, with a target coverage of 75% of students, offers a concrete response to the challenges of promoting local products and strengthening territorialized value chains. The results show that this initiative will make milk production and processing activities profitable, which were previously loss-making, with an annual wealth creation estimated at more than 8,950,000 FCFA. This economic transformation is based on controlled production costs, improved productivity (+12%), stronger organization of local players and economies of scale fostered by the scalingup of canteens. These advances are part of a context in which canteens are becoming a structuring lever for promoting a circular economy, improving producers' incomes and strengthening the resilience of communities in the face of socio-economic challenges. The emergence of new production and processing units, due to the expansion of school canteens, could be organized into cooperatives. This structure would promote the creation of savings and investment mutuals, thus guaranteeing the sustainability of activities beyond the support of technical and financial partners.